y= (x-1)^2 + 2 change this equation into standard form

Question

y= (x-1)^2 + 2

change this equation into standard form

in progress 0
Ayla 22 hours 2021-09-15T01:11:39+00:00 1 Answer 0

Answers ( )

    0
    2021-09-15T01:13:09+00:00

    Answer:

    x² – 2x + 3

    Step-by-step explanation:

    y = (x – 1)² + 2

    = (x – 1)² + 2 [a – b]² = a²- 2ab + b²

    = x²- 2x + 1 + 2

    = x² – 2x + 3

    Thus, the standard form of the equation is x² – 2x + 3

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )